Geology of southeast Alaska : rock and ice in motion - Stowell, Harold Hilton (University of Alaska Press, 2006)
The most powerful forces on earth have shaped the landscape of Southeast Alaska. Scientists and visitors from around the world trek north to experience wild rivers, powerful glaciers, and breathtaking mountain peaks. Now, for the first time, a handy guide to the region is available. Complete with color illustrations revealing millions of years of geological history and in-depth descriptions of Sitka, Juneau, and Glacier Bay, Geology of Southeast Alaska is essential reading for anyone fascinated by rock and ice in motion. Written by a geologist with over twenty-five years of experience in the no.